Three-Dimensional Simulation of the Shrinkage Behavior of Injection-Molded Poly Lactic Acid (PLA): Effects of Temperature, Shear Rate and Part Thickness - Guo, Wenhe; Yang, Bin; Xia, Ru; Su, Lifen; Miao, Jibin; Qian, Jiasheng; Chen, Peng; Yu, Xuekang; Zhang, Qianlei; Deng, Shuangquan (Journal of Research Updates in Polymer Science, 2013)
The effects of injection temperature, shear and part thickness on the linear shrinkage of injection-molded poly (lactic acid) (PLA) were intensively analyzed using the Autodesk Moldflow software. The obtained results showed that both melt temperature and shear rate had obvious effects on the linear shrinkage of PLA, i.e., the linear shrinkage of PLA increases significantly with the increase of melt temperature and shear rate. In addition, the shrinkage of high-crystallinity PLA was remarkably larger than that of low-crystallinity PLA, and thin-walled parts was larger than thick-walled ones in shrinkage.